2021
DOI: 10.3389/fimmu.2021.673692
|View full text |Cite
|
Sign up to set email alerts
|

ROS/RNS Balancing, Aerobic Fermentation Regulation and Cell Cycle Control – a Complex Early Trait (‘CoV-MAC-TED’) for Combating SARS-CoV-2-Induced Cell Reprogramming

Abstract: In a perspective entitled ‘From plant survival under severe stress to anti-viral human defense’ we raised and justified the hypothesis that transcript level profiles of justified target genes established from in vitro somatic embryogenesis (SE) induction in plants as a reference compared to virus-induced profiles can identify differential virus signatures that link to harmful reprogramming. A standard profile of selected genes named ‘ReprogVirus’ was proposed for in vitro-scanning of early virus-induced reprog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(56 citation statements)
references
References 148 publications
3
53
0
Order By: Relevance
“…Ethanol has been shown to reduce ROS levels and led to high induction of alternative oxidase (AOX) and glutathione-S-transferase transcripts (Nguyen et al, 2017). Transcriptome analyses at 2,4-dichlorophenoxyacetic acid (2,4-D) induced reprogramming indicated that the extent of aerobic fermentation is connected to cell proliferation and is regulated by interacting levels of sucrose and AOX (Costa et al, 2021). Transient upregulation of genes related to alcoholic and lactic acid fermentation is shown to be associated with glycolysis and modified complex stress signaling patterns with enhanced superoxide dismutase (SOD) and decreased transcript levels of nitric oxide (NO) producing nitrate reductase (NR).…”
Section: Multifunctional Role Of Aox As Switch Between Respiration and Fermentation During The Germination Processmentioning
confidence: 99%
See 4 more Smart Citations
“…Ethanol has been shown to reduce ROS levels and led to high induction of alternative oxidase (AOX) and glutathione-S-transferase transcripts (Nguyen et al, 2017). Transcriptome analyses at 2,4-dichlorophenoxyacetic acid (2,4-D) induced reprogramming indicated that the extent of aerobic fermentation is connected to cell proliferation and is regulated by interacting levels of sucrose and AOX (Costa et al, 2021). Transient upregulation of genes related to alcoholic and lactic acid fermentation is shown to be associated with glycolysis and modified complex stress signaling patterns with enhanced superoxide dismutase (SOD) and decreased transcript levels of nitric oxide (NO) producing nitrate reductase (NR).…”
Section: Multifunctional Role Of Aox As Switch Between Respiration and Fermentation During The Germination Processmentioning
confidence: 99%
“…Considering the generality of these observations, we proposed a reference transcriptome profile to identify virus traits that link to harmful reprogramming (Arnholdt-Schmitt et al, 2021). This approach helped to identify an early trait for combating SARS-CoV-2 that covers ROS/reactive nitrogen species (RNS) balancing, aerobic fermentation regulation, and cell cycle control (Costa et al, 2021).…”
Section: Multifunctional Role Of Aox As Switch Between Respiration and Fermentation During The Germination Processmentioning
confidence: 99%
See 3 more Smart Citations